Support groups for older people who have been abused : Beyond Existing - Pritchard, Jacki (Violence and abuse series., 2003)
In this thought-provoking book, Jacki Pritchard shows how support groups for victims of elder abuse provide invaluable opportunities for the voices of older people to be heard. Following groups through a two-year period, she discusses how they were set up and the difficulties encountered and overcome, linking these experiences to group work theory. She presents qualitative material alongside guidance for how to undertake practical and therapeutic work with male and female survivors. Presenting t.